Challenges and Opportunities for Deliberative Processes for Healthcare Decision-Making; Comment on "Evidence-Informed Deliberative Processes for Health Benefit Package Design - Part II: A Practical Guide" - Kenneth Bond (Kerman University of Medical Sciences, 2023)
The second edition of the practical guide for evidence-informed deliberative processes (EDPs) is an important addition to the growing guidance on deliberative processes supporting priority setting in healthcare. While the practical guide draws on an extensive amount of information collected on established and developing processes within a range of countries, EDPs present health technology assessment (HTA) bodies with several challenges. (1) Basing recommendations on current processes that have not been well-evaluated and that have changed over time may lead to weaker legitimacy than desired. (2) The requirement for social learning among stakeholders may require increased resourcing and blur the boundary between moral deliberation and political negotiation. (3) Robust evaluation should be based on an explicit theory of change, and some process outcomes may be poor guides to overall improvement of EDPs. This comment clarifies and reinforces the recommendations provided in the practical guide.